The discursive construction of pesticides: between poisons and medicines - García-González, Jaime E. (2026)
This article critically examines the discursive construction of pesticides, particularly the metaphor that frames them as “medicines for plants.” It argues that this linguistic device is not neutral but contributes to downplaying their biocidal nature and reducing public risk perception. Drawing on toxicology, critical epidemiology, and risk communication, the paper shows that pesticides are inherently toxic substances with potential impacts on human health and ecosystems. The study further explores how language shapes the legitimacy of chemically dependent agricultural models by presenting pesticides as therapeutic solutions. It also addresses issues such as biological resistance and technological dependency, which challenge the notion of pesticides as effective and sustainable treatments. From an ethical perspective, the article analyzes the responsibilities of public authorities, professionals, and commercial actors in risk communication, emphasizing the need for conceptual accuracy, transparency, and the precautionary principle. It concludes that accurately naming these substances is essential for informed decision-making in public health, sustainability, and agricultural policy.